2017
DOI: 10.1186/s12902-016-0152-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and determinants of thyroid autoimmunity in Ghanaian type 2 diabetes patients: a case-control study

Abstract: BackgroundThe link between type 1 diabetes and thyroid autoimmunity is well described. The same cannot be said for type 2 diabetes where results have been mixed so far. We investigated the prevalence and determinants of thyroid autoimmunity among Ghanaian type 2 diabetes patients.MethodsThis was a case-control study involving 302 type 2 diabetes patients and 310 non - diabetic controls aged 40–80 years. Anthropometric and blood pressure measurements were obtained. Fasting samples were analyzed for glucose, thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
3
25
1
Order By: Relevance
“…It is worth to note that very impress prevention of T2DM is necessary to reduce the increases rate of thyroid in the population. Further, the current subjects with T2DM also had a higher prevalence and larger thyroid nodules size which is confirmative with an earlier reported strong correlations between insulin resistance and thyroid nodule size (Al-Wazzan et al, 2010;Sarfo-Kantanka et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It is worth to note that very impress prevention of T2DM is necessary to reduce the increases rate of thyroid in the population. Further, the current subjects with T2DM also had a higher prevalence and larger thyroid nodules size which is confirmative with an earlier reported strong correlations between insulin resistance and thyroid nodule size (Al-Wazzan et al, 2010;Sarfo-Kantanka et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, T2DM and thyroid dysfunction are highly correlated as the two commonest endocrinological medical conditions reported in clinical practice (Akbar et al, 2006;Marrero, 2009;Papazafiropoulou et al, 2010;Ghazali & Abbiyesuku, 2010;Wang et al, 2015;Centeno Maxzud et al, 2016;Sarfo-Kantanka et al, 2017;Malaguarnera et al, 2017). Further, some authors indicated that thyroid volume are associated with iodine deficiency and supply, Body Mass Index, gender, age, cigarettes smoking, genetic factors, FBG and T2DM severity (Bener et al, 2009;Duran et al, 2014;Kir et al, 2018;Rezzonico et al, 2008;Bener et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations